2022
DOI: 10.1093/cei/uxac051
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of pathogenic Th17 cells and diminished function of CD69+ Treg lymphocytes in patients with overweight

Abstract: A low-grade inflammatory phenomenon is a feature of overweight and metabolic syndrome. The involvement of a pro-inflammatory Th17 lymphocyte subset and the CD69 + T regulatory (Treg) cell subtype in patients with metabolic dysfunction associated or not to overweight has not been fully elucidated. The aim of this study was to perform a quantitative and functional analysis of pathogenic Th17 lymphocytes and CD69 + Treg cells in patients with metabolic dysfunction (insulin resistance and dyslipidemia). The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The proportion of Tregs rose from 0.79% in NG to 2.48% in HG, and they highly expressed the level of CD69 . As we know, CD69+Tregs play a critical role in the maintenance of immunologic tolerance and suppression of innate immune responses ( 41 ). We also found higher proportions of two subclusters (CD4 TCM and CD8 TCM) with high expression of GATA3 that contributed to the maintenance of immune activity ( 42 ) under high stress.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of Tregs rose from 0.79% in NG to 2.48% in HG, and they highly expressed the level of CD69 . As we know, CD69+Tregs play a critical role in the maintenance of immunologic tolerance and suppression of innate immune responses ( 41 ). We also found higher proportions of two subclusters (CD4 TCM and CD8 TCM) with high expression of GATA3 that contributed to the maintenance of immune activity ( 42 ) under high stress.…”
Section: Discussionmentioning
confidence: 99%
“…As in the case of Treg cells, several studies have shown abnormal levels of Th17 cells in the peripheral blood from patients with T2DM [ 38 ]. Both increased and normal levels of CD4 + IL-17 + lymphocytes have been detected in these patients [ 16 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…12 In a recent experimental study, an increase of Th17 cells and a reduction of CD69+ regulatory T cells (T reg) were demonstrated in people with metabolic dysfunction showing dyslipidemia and insulin resistance. 13 The number of pathogenic Th17 cells was mainly increased in people that were also overweight.…”
Section: Comor Bidit Y I N Psor I Atic Dise Asementioning
confidence: 99%